2010
DOI: 10.1371/journal.pone.0011349
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure of the Mouse Germ Line: DNA Adducts in Spermatozoa and Formation of De Novo Mutations during Spermatogenesis

Abstract: BackgroundSpermatozoal DNA damage is associated with poor sperm quality, disturbed embryonic development and early embryonic loss, and some genetic diseases originate from paternal de novo mutations. We previously reported poor repair of bulky DNA-lesions in rodent testicular cells.Methodology/Principal FindingsWe studied the fate of DNA lesions in the male germ line. B[a]PDE-N2-dG adducts were determined by liquid chromatography-tandem mass spectrometry, and de novo mutations were measured in the cII-transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 59 publications
6
40
2
2
Order By: Relevance
“…Moreover, recent studies have demonstrated that BaP can impair functional parameters in sperm, induce DNA strand breaks in sperm, and increase the proportion of apoptotic germ cells [50,51]. Furthermore, studies using the TGR assay have revealed that BaP induces point mutations in different germ cells [40][41][42]. In this study, we demonstrate that mice treated with 100 mg/kg of BaP exhibit mutation induction at a microsatellite locus in spermatogonia and that the magnitude of the effect is similar to that observed with an acute exposure to ENU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies have demonstrated that BaP can impair functional parameters in sperm, induce DNA strand breaks in sperm, and increase the proportion of apoptotic germ cells [50,51]. Furthermore, studies using the TGR assay have revealed that BaP induces point mutations in different germ cells [40][41][42]. In this study, we demonstrate that mice treated with 100 mg/kg of BaP exhibit mutation induction at a microsatellite locus in spermatogonia and that the magnitude of the effect is similar to that observed with an acute exposure to ENU.…”
Section: Discussionmentioning
confidence: 99%
“…We test the efficacy of this SM-PCR approach by determining mutation frequencies in the sperm of mice exposed to N-ethyl-N-nitrosourea (ENU), a prototypical germ-cell mutagen tested by both the TGR [12,14,16,36] and ESTR [19,37,38] assays, and benzo(a)pyrene (BaP), a common environmental pollutant [39] following spermatogonial exposure. BaP is an established somatic-cell mutagen [39], and there is also evidence that BaP induces germ cell mutations [40][41][42], but there is currently no evidence that BaP induces tandem repeat mutations through the male germline. We demonstrate that SM-PCR analysis of unstable microsatellites by capillary electrophoresis can be used to detect changes in germline mutation frequencies arising in chemically treated spermatogonia.…”
Section: Introductionmentioning
confidence: 99%
“…Either way, metabolites react with a multitude of molecules and thus exposure to B[a]P may disturb many cellular processes. Previous reports probably reflecting the genomic effects of B[a]P have described DNA lesions in mouse sperm after in vivo treatment (Olsen et al 2010) and similar non-genomic BPDE-induced damage in human sperm following in vitro exposure (Sipinen et al 2010). Surprisingly, B[a]P and BPDE-related DNA fragmentation were also observed in human sperm in vitro as measured by the alkaline comet assay.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 69%
“…2) [63][64][65]. DNA lesions are not repaired in late spermatids and spermatozoa as excision repair pathways are no longer active in these cell types [15,[66][67][68]. Sperm with high levels of DNA damage can still be capable of fertilisation, leading to impaired development of the zygote, early abortion, and problems in the offspring including congenital malformations [69] and diseases such as cancer [66,70].…”
Section: Transgenerational Effectsmentioning
confidence: 99%